The Legal Study of Materiil Testing Rights Supreme Court in Indonesia - Ni Luh Gede Astariyani (Focus Journal : Law Review, 2022)
The authority of the Supreme Court to examine statutory regulations under the law or in this case referred to as judicial review is a mandate of the 1945 Constitution. Article 24A paragraph (1) of the 1945 Constitution which is the result of the Third Amendment states, "The Court The Supreme Court has the authority to judge at the level of cassation, examine the legislation under the law against the law, has other powers granted by law. From these provisions it is clear that the 1945 Constitution provides 3 (three) categories of authority to the Supreme Court, namely (1) adjudicating at the level of cassation, (2) examining statutory regulations under the law against the law, and (3) other powers granted by law. Specifically for the third provision, the 1945 Constitution stipulates that the authority of the Supreme Court is open, which means that it is possible to increase the authority of the Supreme Court as long as it puts the regulation of the additional authority into or by law. The examination is carried out on a statutory provision against a higher statutory regulation or against the constitution as the highest law. That is, judicial review works on the basis of legal norms or statutory regulations that are hierarchically structured. Without this hierarchy, it is impossible to conduct a judicial review. At this time in Indonesia the hierarchy of laws and regulations is regulated in Article 7 of Law no. 12 of 2011 concerning the Establishment of Legislation.